Examining online international health professions education: a mixed methods review of barriers, facilitators, and early outcomes. - Dell'Aiera, Laura; Fitzgerald, David; Fisher, David; Gill, Norman W. (Journal of Extra-Corporeal Technology, 2024)
Background: Access to quality healthcare education across the world is disproportionate. This study explores the potential for Cardiovascular Perfusion education to be delivered online to reach international students. Methods: Exploratory mixed methods were used to identify the barriers, facilitators, and early outcomes of online international health professions education. Results: Qualitative analysis yielded four primary and nine subthemes. Multiple interventions were implemented in the planning of a novel online international Extracorporeal Science (ECS) program based on these themes. Quantitative data from the first semester of the new ECS program was collected along with data from the traditional entry-level program and historic data from previous entry-level cohorts. No significant correlations or differences were found between students. Student satisfaction surveys were determined to be equivalent for each group. Mixed data analysis revealed exceptional student satisfaction in areas where qualitative feedback was incorporated into the program design. Conclusions: Online international education may be a viable option in the health professions. Barriers and facilitators to this mode of education were identified and utilized in designing one such program. Early outcomes from the novel ECS program reveal that student performance and satisfaction are equivalent to those of a traditional in-person training program.